Optimizing sample size for molecular characterization of open-pollinated maize (Zea mays L.) varieties using simple sequence repeat markers - Arafayne, G.; Menkir, A.; Adetimirin, Victor O.; Gedil, Melaku A (Springer, 2018)
Molecular-based characterization of open-pollinated varieties (OPVs) in maize is useful to define their unique profiles. A total of 58 SSR markers selected from a panel of 70 were used for genotyping three samples of 30, 50 and 100 plant bulks for each of 32 OPVs. The SSR markers detected a total of 253 alleles in the 32 maize OPVs across the three bulk samples. The number of alleles per marker varied from 2 to 7, with an overall mean of 4.36. The genetic distance among the OPVs varied from 0.17 to 0.93 with an average of 0.70 ± 0.007 for bulk samples of 30 plants, 0.20 to 0.91 with an overall mean of 0.70 ± 0.007 for bulk samples of 50 plants and from 0.30 to 0.95 with an average of 0.75 ± 0.006 for bulk samples of 100 plants. Cluster analysis separated the 32 maize OPVs into two major groups, which were further separated into two sub-groups for each type of bulk sample. The groupings of the OPVs into two major groups and their corresponding sub-groups was consistent with known breeding history (common parentage) and common target traits during development of the OPVs irrespective of the sample size used. However, in the bulk samples of 50 and 100 plants, some sub-groups were composed of OPVs with mixed maturity classes and diverse genetic backgrounds. Of the three independent bulk samples, the smallest sample size of 30 plants was found to be optimal for characterizing heterogeneous and heterozygous maize populations and OPVs owing to its cost-effectiveness and relative ease of sample processing.